The legal regulation of Paraguay's religious status : ¿Non denominational or secular State? (Legal journal - Research in Legal and Social Sciences, 2020)
This work aims to deliver a comprehensive analysis of the religious fact and its interaction with the paraguayan legal order, from the historical and current perspective, given the fact the the currect system could not be conceived without studying, visualizing, and comprehending those that preceded them. In addition, it is thereby seeked to give a response to the most controversial questions that underlie in the society and move to the political and legal atmosphere, such as the relationship State-Church and the different minority religious confessions. Furthermore, this paper also intends to highlight the lack of research in this little known, but important field within paraguayan legal doctrine, which is completed with international convention signed by the republic and also with the search in comparative law, for formulations and preceps that help clarify or enhance the system currently established.
Keywords: State; denominational; non-denominational; secular; freedom of religion